Comparative study of 4-((4-aminophenyl)diazenyl)-2-((2-phenylhydrazono)methyl)phenol and N-(4-((4-hydroxy-3-((2-phenylhydrazono)methyl)phenyl)diazenyl)phenyl)acetamide - DFT method - Siluvairaj, Richard Rajkumar; Govindasamy, Vallal Perumal; Govindasamy, Rajarajan; Chinnappan, Periyanayagasamy Vanathu; Venugopal, Thanikachalam (European Journal of Chemistry, 2024)
Theoretical calculation of 4-((4-aminophenyl)diazenyl)-2-((2-phenylhydrazono)methyl) phenol (1) and N-(4-((4-hydroxy-3-((2-phenylhydrazono)methyl)phenyl)diazenyl)phenyl) acetamide (2) was studied by DFT/B3LYP/6-311+G(d,p) basis set. The calculated values of geometric structural parameters, Fourier transform infrared spectral data, highest occupied molecular orbital and lowest unoccupied molecular orbital, natural bond orbital, nucleus-independent chemical shifts, Fukui function, polarizability, hyperpolarizability, and UV data of compounds 1 and 2 clearly indicate that substitution of the amino group alters the physical properties of compound 2. The nucleus-independent chemical shift values of the amino-substituted phenyl ring reduces the aromatic character due to the lone pair electron on nitrogen involved in inductive and conjunction effects, as well as due to OH, NH2 and OH, NHCOCH3 in compounds 1 and 2, respectively. The effect of the solvent on different parameters was studied, and it was found that increasing the dielectric constant increased the parameter studied. The stability and planarity of the molecule’s effects on dipole moment, energy, polarizability, and hyperpolarizability were studied extensively.